(untitled) (Bangladesh Journal of Nuclear Medicine, 2025)
Background: Differentiated thyroid carcinoma (DTC) which includes both papillary and follicular subtypes, is a type of thyroid cancer that has a high probability of being differentiated thyroid carcinoma entails a total thyroidectomy, followed by radioactive iodine ablation (RAIA), and then the administration of suppressive dose levothyroxine. Patients with long term TSH suppression might be at risk for developing osteoporosis, experiencing a loss of bone mass, and eventually experiencing a decrease in bone mineral density. Objective: To determine the effects of long term TSH suppressive dose of levothyroxine on bone mineral density in patients with differentiated thyroid carcinoma after radioactive iodine ablation. Patients and Methods: This descriptive observational study was conducted in National Institute of Nuclear Medicine & Allied Sciences (NINMAS), Bangladesh for eighteen months and the study population was the differentiated thyroid carcinoma patients with history of total thyroidectomy followed by radioactive iodine ablation. The age ranged from 20 to 45 years who has history of long term TSH suppressive doses of levothyroxine for more than five years. Bone mineral density was measured at the lumbar spine (L1-L4 vertebrae), right (Rt.) femoral neck, and left (Lt.) femoral neck. The study’s results provide insights into the clinical attributes of the participants, their bone mineral density status, and the correlations of duration of levothyroxine’s treatment with bone mineral density. Result: Most patients were premenopausal (35-39- and 40-45-years age groups), female (84%), and overweight and obese. In this study, the total number of differentiated thyroid carcinoma patients was 118, with a mean age of 37.08 ± 5.48 years for levothyroxine suppression therapy. The majority of individuals, namely 108 out of 118, adhere to a levothyroxine medication regimen for 15 years. The study examined the bone mineral density status in the participants’ lumbar spine, as determined by the T-score and Z-score. Out of the total 108 subjects, 62% had normal bone mineral density, 24% had osteopenia, and 4% had osteoporosis. Based on the T-score, the results indicated that a majority of people (67%) exhibited normal bone mineral density, while the other participants had low bone mineral density. Within the low bone mineral density group, 29% of people had osteopenia, whereas 4% developed osteoporosis. Regarding the femoral neck (Rt.) and femoral neck (Lt.), the majority of subjects, 97% and 94%, respectively, had normal bone mineral density, whereas the remaining participants had low bone mineral density (both osteopenia and osteoporosis). The study found that 6.7% of patients had low bone mass in their lumbar spine, while the rest had normal bone mass. There was no significant association between levothyroxine therapy duration and bone mineral density scores in either lumbar spine or femoral necks. Conclusion: Despite concerns regarding TSH suppression and its potential impact on bone metabolism, our study suggests that prolonged levothyroxine therapy does not adversely affect bone mineral density. Bangladesh J. Nuclear Med. 27(2): 185-190, 2024